Kajian Hukum Tindak Pidana Kekerasan Dalam Rumah Tangga Yang Dilakukan Suami terhadap Isteri Ditinjau Dari Aspek Psikologi Kriminal - Bela Safira Sinaga; Muazzul Muazzul; Wessy Trisna (Universitas Medan Area, 2021)
Domestic violence is any act against someone, especially women, which results in physical, sexual, psychological, and / or neglect of the household, including threats to commit acts, coercion, or illegal deprivation of liberty within the scope of the household. The research method used is normative legal research with descriptive analysis research characteristics. Based on research on the role of criminal psychology against perpetrators of domestic violence committed by husbands against wives, there is a Psychiatric Visum et Repertum (VeR) which is made to explain a person's mental status using psychiatry and based on the results of psychiatric examinations for the benefit of law enforcement. As well as the law enforcement process against perpetrators of domestic violence if it is related to the criminal psychology of criminals. So it is hoped that criminal psychology can be a consideration for law enforcement officials in resolving a case. Both from the psychological side of the perpetrator and the victim's psychological, thus criminal psychology can be used as a benchmark in imposing punishment in accordance with the crime committed by the perpetrator in accordance with their psychology. Therefore, it is also hoped that law enforcers will understand psychological concepts.